Response of Intraspecific Crosses in F1 and their Deterioration in F2 Generation of Bread Wheat (Triticum aestivum L.) - Z.A, Soomro; Khalid, M; Abro, T.F; Mangrio, G.S; Channa, S.A; Kasi, U.A; Shar, P.A; Hassni, M.D; Shah, R.A (International Journal of Sustainable Agricultural Research, 2019)
The experimental trail was conducted at Wheat and barley Research Institute, Tandojam. The seed of nine parents along with their six F1 and F2 generations were sown in Randomized Complete Block Design (RCBD) with three replications. The varieties used in the experiment were Sassui, Abadgar, Maxipak, Soghat, Marvi, Noori, Moomal, Anmol-91 and Mehran. The mean squares regarding the grains spike-1, grain yield plant-1, and seed index exhibited that parents, crosses, F1 and F2 hybrids were highly significant at 0.01 level of probability. Among the parents, Mehran gave highest value for grain yield plant-1, while F1 hybrid Moomal × Anmol-91 displayed maximum grain yield plant-1. The results for grain yield plant-1, displayed that highest heterosis (87.22%) and heterobeltiosis (86.80%) was exhibited by the cross Maxipak × Soghat. The maximum inbreeding depression (16.23%) for the said trait was shown by the cross Sassui × Abadgar. The cross Maxipak × Soghat could be selected for further evaluation in advanced segregating generations.